Handbook of Heterogeneous Catalysis 2008
DOI: 10.1002/9783527610044.hetcat0123
|View full text |Cite
|
Sign up to set email alerts
|

Solid Catalysts for the Oxidation of Volatile Organic Compounds

Abstract: The sections in this article are Introduction Significance of the Problem Applications of Catalytic Oxidation for VOC Control Catalytic Oxidation Scope of this Chapter Reactors and Process Configurations for Catalytic Oxidation System… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…The catalytic oxidation is the most attractive way to remove VOCs at low concentrations from industrial gaseous effluents [3], and it has shown to be a potential method also in the case of SVOCs [4].…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic oxidation is the most attractive way to remove VOCs at low concentrations from industrial gaseous effluents [3], and it has shown to be a potential method also in the case of SVOCs [4].…”
Section: Introductionmentioning
confidence: 99%
“…removal of VOCs) and fine chemical industry [1][2][3]. These oxidation processes involve the conversion of the corresponding chemicals into intermediates (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different transition metal catalysts, Ti-based systems have been the most widely investigated. Besides the Shell catalyst based on Ti(IV)-SiO 2 , there have been numerous efforts to design variously substituted Ti(IV)-framework materials, e.g. TS-1, Ti-MCM41, etc., with excellent catalytic performance in the aforementioned peroxo-acid oxidized reactions [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%